2021
DOI: 10.1109/access.2021.3135600
|View full text |Cite
|
Sign up to set email alerts
|

Single-Trace Attack on NIST Round 3 Candidate Dilithium Using Machine Learning-Based Profiling

Abstract: In this paper, we propose single-trace side-channel attacks against CRYSTALS-DILITHIUM. CRYSTALS-DILITHIUM is a lattice-based digital signature algorithm, one of the third round finalists of the national institute of standards and technology (NIST) standardization project. We attack number-theoretic transform (NTT) in the signing procedure and key generation of CRYSTALS-DILITHIUM to obtain a secret key. When targeting the signing procedure, we can recover both secret key vectors s 1 and s 2 . This enables forg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Primas et al (2017) proposed a generic method targeting NTT operations that requires establishing templates for all possible multiplications in butterfly operations, which is costly. Han et al (2021) employed a machine learning-based method to attack NTT operations, recovering keys using 60,000 power traces. Berzati et al (2023) reconstructed a given coefficient in a predicted vector to determine if it is zero, thus recovering the private key using linear algebra methods, with 700,000 power traces.…”
Section: Related Workmentioning
confidence: 99%
“…Primas et al (2017) proposed a generic method targeting NTT operations that requires establishing templates for all possible multiplications in butterfly operations, which is costly. Han et al (2021) employed a machine learning-based method to attack NTT operations, recovering keys using 60,000 power traces. Berzati et al (2023) reconstructed a given coefficient in a predicted vector to determine if it is zero, thus recovering the private key using linear algebra methods, with 700,000 power traces.…”
Section: Related Workmentioning
confidence: 99%
“…Han et al [162] targeted the NTT instance over s 1 using a simple template attack, which could recover the complete secret polynomial s 1 in a single trace. They showed that an attacker can target leakage from the product of the secret coe cients with the twiddle factors in the first round of the NTT (i.e.)…”
Section: Simple Template Attacksmentioning
confidence: 99%
“…Moreover, the attack is aided by the fact that there are only 5 possible candidates for coe cients of the secret s 1 . Han et al [162] targeted the reference implementation of Dilithium through the power side-channel on the ARM Cortex-M4 microcontroller to recover the entire secret s 1 in a single trace. We refer to this attack as the Simple_NTT_Template attack.…”
Section: Simple Template Attacksmentioning
confidence: 99%